2016
DOI: 10.1021/acs.est.6b00998
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of the Synergistic Antibacterial Activity of Combined Silver Nanoparticles and Common Antibiotics

Abstract: A combination of silver nanoparticles (AgNPs) and an antibiotic can synergistically inhibit bacterial growth, especially against the drug-resistant bacteria Salmonella typhimurium. However, the mechanism for the synergistic activity is not known. This study chooses four classes of antibiotics, β-lactam (ampicillin and penicillin), quinolone (enoxacin), aminoglycoside (kanamycin and neomycin), and polykeptide (tetracycline) to explore their synergistic mechanism when combined with AgNPs against the multidrug-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(160 citation statements)
references
References 52 publications
10
150
0
Order By: Relevance
“…The mechanisms proposed involve the formation of chemical bonds among the antibiotic molecules and the AgNP surfaces, which work as a drug delivery systems. [31][32][33][34][35][36]49,50 Such propositions are in agreement with the assumption here presented, since the three used drugs have antibacterial activities involving intracellular interference in the metabolism of DNA or RNA. Their uptakes take place due to the affinity of silver surfaces for the bacterial membranes, probably followed by the release of the antibiotic molecules in the intracellular medium due to the oxidation of the AgNP surfaces.…”
Section: Resultssupporting
confidence: 88%
“…The mechanisms proposed involve the formation of chemical bonds among the antibiotic molecules and the AgNP surfaces, which work as a drug delivery systems. [31][32][33][34][35][36]49,50 Such propositions are in agreement with the assumption here presented, since the three used drugs have antibacterial activities involving intracellular interference in the metabolism of DNA or RNA. Their uptakes take place due to the affinity of silver surfaces for the bacterial membranes, probably followed by the release of the antibiotic molecules in the intracellular medium due to the oxidation of the AgNP surfaces.…”
Section: Resultssupporting
confidence: 88%
“…Studies showed that the antimicrobial properties of Ag materials rely on free Ag ions, which can not only bind to sulfur, oxygen, and nitrogen of essential enzymes, resulting in bacterial cell death, but also react with DNA to prevent unwinding, resulting in serious damage to bacterial cells. 29,50,51 Moreover, the Ag NPs itself can directly deactivate the sulfur-containing proteins of cell membrane, causing functional damage to the membrane and the structural changes. 52 On the other hand, vancomycin is a potent antibiotic against Gram-positive bacteria and exerts antibacterial activity by forming hydrogen bonds with the peptidoglycan terminus D-Ala-D-Ala on the cell wall.…”
Section: @Ag Microflowersmentioning
confidence: 99%
“…[27][28][29][30] For example, Brown et al indicated the effective synergistic effect of noble metal NPs functionalized with ampicillin against multiresistant strains. 31 Lai et al reported a general route for preparing vancomycin-modified Au NPs; the products act as effective broad-spectrum bactericides against both Gram-negative and Gram-positive pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al have shown the synergic effect of amoxicillin with silver nanoparticles against Escherichia coli . Rai et al used cefaclor as both reducing and capping agent to produce spherical gold nanoparticles and showed a potent activity against both Gram‐positive and Gram‐negative bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we combined AuNPs with DOXY by three chemical different methodologies (DOXY‐AuNPs, DOXY‐ON‐AuNPs, DOXY IN‐AuNPs) and, evaluated the antimicrobial effect of these hybrids on several bacterial species in the presence of AuNPs synthesized. Therefore, the development of a simple and fast method to improve the activity of DOXY and oxytetracycline has become increasingly attractive …”
Section: Introductionmentioning
confidence: 99%